Evaluasi Kinerja Billingsystem Rawat Inap Menggunakan Kerangka Pieces - Jihan Anfa; Djazuly Chalidyanto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
The occurrence of patient dissatisfaction in Wiyung Sejahtera Hospital associated with the duration in providing the hospitalization bills information shows 90.26% in January to November 2014. This research aimed to analyze the knowledge, necessity of skills training and human resource needed related to billingsysteminevaluating the performance of billing system through user’s perspective by using PIECES Framework. This isdescriptive analytic studywith cross-sectional design. Information obtained from 57 respondents, which inputand verifies bills on the application billingsystem hospitalization. The result showed that the knowledge of billingsystemusers is good, the necessity of IT training is not fulfilled and user’s skills is not good. Billingsystemhospitalization performance evaluation using PIECES Framework results for all indicators are constraints; Performancemean 2,6667; Informationmean 2,8319; Economymean 2,6901; Controlmean 2,7544; Efficiency mean 2,7661 and Servicemean 2,8596. There is a strong correlation between training toward users knowledge about billingsystem. In order to improve the quality of service, it is urgently required to hospital itself providing training to users, developing into a fully package integrated system and arranging standard operating procedures.Keywords: billingsystemperformance, evaluation,PIECES framework